Interglacial microrefugia and diversification of a cactus species complex: phylogeography and palaeodistributional reconstructions for Pilosocereus aurisetus and allies - Bonatelli, Isabel A. S; Perez, Manolo F; Peterson, A. Townsend; Taylor, Nigel P; Zappi, Daniela C; Machado, Marlon C; Koch, Ingrid; Pires, Adriana H. C; Moraes, Evandro M (Molecular ecology, 2014)
The role of Pleistocene climate changes in promoting evolutionary diversification in global biota is well documented, but the great majority of data regarding this subject come from North America and Europe, which were greatly affected by glaciation. The effects of Pleistocene changes on cold‐ and/or dry‐adapted species in tropical areas where glaciers were not present remain sparsely investigated. Many such species are restricted to small areas surrounded by unfavourable habitats, which may represent potential interglacial microrefugia. Here, we analysed the phylogeographic structure and diversification history of seven cactus species in the Pilosocereus aurisetus complex that are restricted to rocky areas with high diversity and endemism within the Neotropical savannas of eastern South America. We combined palaeodistributional estimates with standard phylogeographic approaches based on two chloroplast DNA regions (trnT‐trnL and trnS‐trnG), exon 1 of the nuclear gene PhyC and 10 nuclear microsatellite loci. Our analyses revealed a phylogeographic history marked by multiple levels of distributional fragmentation, isolation leading to allopatric differentiation and secondary contact among divergent lineages within the complex. Diversification and demographic events appear to have been affected by the Quaternary climatic cycles as a result of isolation in multiple patches of xerophytic vegetation. These small patches presently harbouring P. aurisetus populations seem to operate as microrefugia, both at present and during Pleistocene interglacial periods; the role of such microrefugia should be explored and analysed in greater detail.